If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3x+7=7(1+8x)
We move all terms to the left:
-3x+7-(7(1+8x))=0
We add all the numbers together, and all the variables
-3x-(7(8x+1))+7=0
We calculate terms in parentheses: -(7(8x+1)), so:We get rid of parentheses
7(8x+1)
We multiply parentheses
56x+7
Back to the equation:
-(56x+7)
-3x-56x-7+7=0
We add all the numbers together, and all the variables
-59x=0
x=0/-59
x=0
| 3(d-6)-7=19 | | -7.6-15.1f=16.98-12f+12.93 | | 32=112/x-2x | | 6r−12=3r+15 | | 3x+2x-7=180 | | 6+17k=-16+19k | | 4x+7-6=-11+2x | | 3×a=20 | | -7-5x=1-5x | | 17v+19=18v-17+18 | | d2−4d=−3 | | 0.9n=5.4 | | 2(5c+1)=6 | | 7p+-12=72 | | x-8-8x=-8-7x | | -4y+18=-4y+8 | | 40=-5(x-6) | | -4y+18=-4y+18 | | -10(z+5)=42-4(2z+7) | | 4(q-76)=84 | | 2x−4+5x=8x+6+x−2 | | |-2x+8|=16 | | 54=-9(c-1) | | 360-4y+44=40y-28 | | 4.75x=9.5x | | 23=25-2t | | -42-9x=42-3x | | -7v+2=5-8v | | -14=-z/2-11 | | 21x-6=18x+5 | | 2(n-73)=50 | | -9x-35=0 |